Innovation in the small business system of the service sector is the key to creating entrepreneurship and innovation - Ulmasova Oygul Bakhtiyarovna (THE INNOVATION ECONOMY, 2026)
This article emphasizes that innovative entrepreneurship in the service sector, especially in small businesses, is a separate creative process of creating innovations in small enterprises, and its basis is the constant search for new opportunities, focus on innovation, and the implementation of new projects in small enterprises.